Antimicrobial Resistance, Biofilm Formation, and Virulence Determinants in Enterococcus faecalis Isolated from Cultured and Wild Fish - Md. Liton Rana; Zannatul Firdous; Farhana Binte Ferdous; Md. Ashek Ullah; Mahbubul Pratik Siddique; Md. Tanvir Rahman (MDPI AG, 2023)
Fish has always been an integral part of Bengali cuisine and economy. Fish could also be a potential reservoir of pathogens. This study aimed to inquisite the distribution of virulence, biofilm formation, and antimicrobial resistance of Enterococcus faecalis isolated from wild and cultivated fish in Bangladesh. A total of 132 koi fish (Anabas scandens) and catfish (Heteropneustes fossilis) were collected from different markets in the Mymensingh district and analyzed to detect E. faecalis. E. faecalis was detected by conventional culture and polymerase chain reaction (PCR), followed by the detection of virulence genes by PCR. Antibiotic susceptibility was determined using the disk diffusion method, and biofilm-forming ability was investigated by crystal violet microtiter plate (CVMP) methods. A total of 47 wild and 40 cultured fish samples were confirmed positive for E. faecalis by PCR. The CVMP method revealed four per cent of isolates from cultured fish as strong biofilm formers, but no strong producers were found from the wild fish. In the PCR test, 45% of the isolates from the wild and cultivated fish samples were found to be positive for at least one biofilm-producing virulence gene, where agg, ace, gelE, pil, and fsrC genes were detected in 80, 95, 100, 93, and 100% of the isolates, respectively. Many of the isolates from both types of samples were multidrug resistant (MDR) (73% in local fish and 100% in cultured fish), with 100% resistance to erythromycin, linezolid, penicillin, and rifampicin in E. faecalis from cultured fish and 73.08, 69.23, 69.23, and 76.92%, respectively, in E. faecalis from wild fish. This study shows that E. faecalis from wild fish have a higher frequency of virulence genes and biofilm-forming genes than cultivated fish. However, compared to wild fish, cultured fish were found to carry E. faecalis that was more highly multidrug resistant. Present findings suggest that both wild and cultured fish could be potential sources for MDR E. faecalis, having potential public health implications.